تقييم واقع ممارسات سلسلة التوريد في شركات صناعة الأدوية السورية "دراسة ميدانية" - طرابلسية شيراز; قعير سومر (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The aim of this research is to assess the reality of supply chain practices (relationship with suppliers, customer relationship, relationship with intermediaries and distributors) in pharmaceutical companies in Syria. The research was based on the descriptive approach, and the research community included four pharmaceutical companies (Ibn Zahr, Bahri Medical, Tramadica, Unipharma International Company for Pharmaceutical Industries). The research "questionnaire" them, and (176) questionnaires were retrieved, with a response rate of (88%). The results showed that the companies in question seek to a medium extent to establish relationships with suppliers, intermediaries and distributors, and to a large extent to establish a relationship with customers, within the supply chain practices. هدف البحث إلى تقييم واقع ممارسات سلاسل التوريد المتمثلة بـ (العلاقة مع الموردين, والعلاقة مع العملاء, والعلاقة مع الوسطاء والموزعين) في شركات صناعة الأدوية في سورية. اعتمد البحث على المنهج الوصفي, وشمل مجتمع البحث أربع شركات أدوية (ابن زهر, بحري الطبية, التراميديكا, يونيفارما الشركة العالمية للصناعات الدوائية), أما عينة البحث فهي عينة عشوائية من العاملين في هذه الشركات, حيث بلغت (200) عامل, تمّ توزيع أداة البحث "الاستبانة" عليهم, وتمّ استرجاع (176) استبانة, وبنسبة استجابة بلغت (88%). أظهرت النتائج أنّ الشركات محل الدراسة تسعى وبدرجة متوسطة لإقامة علاقات مع الموردين ومع الوسطاء والموزعين, وبدرجة كبيرة لإقامة علاقة مع العملاء, وذلك ضمن ممارسات سلسلة التوريد.